The relationship between happiness and autonomy on psychological wellbeing among undergraduate students in Klang Valley, Malaysia - Yusof, Nabila; Ma’rof, Aini Azeqa; Rosnon, Mohd Roslan (Human Resources Management Academic Research Society (HRMARS), 2024)
This study examines the intricate connections between happiness, autonomy, and psychological well-being in a culturally varied setting, specifically among undergraduate students in Klang Valley, Malaysia. This research investigates the interaction between selfdetermination theory and the broaden-and-build theory of positive emotions within a hybrid cultural framework that combines individualistic and collectivist principles. The study involved 401 university students who contributed data using validated scales to measure pleasure, autonomy, and psychological well-being. The correlations and predictive capacities of these variables were assessed using quantitative methods, specifically Pearson correlation and multiple regression. The findings demonstrated a notable and meaningful connection between happiness and psychological well-being, confirming the importance of happy emotions in improving mental health. In contrast, autonomy had an intricate correlation with well-being, displaying certain signs of adverse effects possibly stemming from cultural influences and the clash between personal aspirations and societal responsibilities. These findings emphasize the complex relationship between autonomy and psychological health, indicating that in the specific context of Malaysia, having high degrees of autonomy may not necessarily lead to improved psychological well-being. This study enhances the overall comprehension of psychological concepts in non-Western contexts and emphasizes the importance of culturally responsive approaches to mental health that take into account the delicate equilibrium between individual autonomy and collective-oriented principles.